Quality of life in asthmatic children and their caregivers after two-year treatment with omalizumab, a real-life study - Sztafińska, Anna; Jerzyńska, Joanna; Stelmach, Włodzimierz; Woicka-Kolejwa, Katarzyna; Stelmach, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Omalizumab, a monoclonal anti-immunoglobulin E antibody, has been successfully used as a supplementary therapy to improve asthma control in children aged ≥ 6 years with severe persistent allergic asthma. Aim : To demonstrate the quality of life in children with severe asthma and their caregivers, and changes from baseline in forced expiratory volume in 1 s (FEV 1 ) and daily inhaled corticosteroids (ICS) dose after 2-year treatment with omalizumab. Material and methods : Participants were seen in the clinic at enrollment (visit 1), after 16 weeks (visit 2), after 52 weeks (visit 3) and after 104 weeks (visit 4) of treatment with omalizumab. We evaluated lung function, ICS use and the quality of life with the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) and the Pediatric Asthma Caregiver’s Quality of Life Questionnaire (PACQLQ). Results : Nineteen children and caregivers were enrolled. Significant improvement was observed in PAQLQ and PACQLQ scores, both in all domains and in total scores. Significant differences were found between the first and the other visits. A positive correlation between PAQLQ and PACQLQ at the first and at the second visit was found, 63.3% of patients achieved reduction in ICS doses. We did not notice any significant improvement in FEV 1 . Conclusions : The improvement in quality of life in asthmatic children and adolescents observed after omalizumab correlates with the improvement of quality of life in caregivers, reduction in ICS use but not with FEV 1 .